A REVIEW OF MATHEMATICAL MODELING OF CARBON POLLUTION BY VEHICLES ON HIGHWAYS WITH HUGE EMBANKMENTS - Awino, John Otieno; Onyango, Thomas; Okelo, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
In this paper, we review developed mathematical models for carbon pollution and investigatethe level of carbon pollutants on the highways and how it spreads to the people held up in trafficjams and those residing closer to the highways in Kenya.